ISLAMIC-BASED COMMUNITY EDUCATION AND ADULT FUNCTIONAL LITERACY: PARTICIPATION MECHANISMS AND CAPABILITY OUTCOMES FOR SDG 4 IN RURAL INDONESIA - Mohamad Zubaidi; Muhammad Ibrahim; Endah Setiyowati; Nurain Karnain; Saiful Hadi; Sri Nurhayati; Gumpanat Boriboon; Mohammad Moreb; Sameer Mohammed Majed Dandan (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Despite ongoing efforts to expand adult literacy programs under SDG 4, participation and sustained engagement in rural contexts remain uneven, and the mechanisms that support persistence in community-based settings are not well understood. This study examines how faith-based community education supports adult functional literacy participation and perceived outcomes in relation to Sustainable Development Goal 4 (SDG 4) in rural Indonesia. Focusing on Muslimat NU learning activities in Pamekasan, the study investigates adult learners’ motivations for participation, the learning climate, the roles of religious practices and authority, and perceived literacy-related outcomes. The study employed a cross-sectional descriptive survey design involving 64 adult participants. Data were collected through a structured questionnaire capturing participation motivations, perceptions of the learning environment, integration of religious practices, the influence of moral authority, and self-reported literacy and capability outcomes. Data were analyzed using descriptive statistics and qualitative descriptive interpretation of open-ended responses. Findings show that participation was predominantly agentic and instrumental, driven by literacy aspirations and family-related motivations rather than passive compliance. The learning environment was perceived as effectively safe and enjoyable, supporting sustained participation. Religious practices such as prayer and Islamic adab functioned as normative learning infrastructure, structuring continuity and attention. Moral authority, embodied by kyai and nyai figures, operated as non-coercive regulatory capital, reinforcing attendance discipline. Participants also reported perceived improvements in literacy, alongside broader economic and social spillovers. The study contributes to adult literacy research by elucidating socially embedded mechanisms—motivation, affective safety, ritual practice, and moral authority—through which faith-based community settings can support functional literacy engagement in support of SDG 4.